Endoscope-Assisted Combined Supracerebellar Infratentorial and Endoscopic Transventricular Approach to the Pineal Region: A Technical Note - Felbaum, Daniel (Cureus, 2016)
Neoplasms of the pineal region comprise less than 2% of all intracranial lesions. A variety of techniques have been adapted to gain access to the pineal region. Classic approaches employ the use of the microscope. More recently, the endoscope has been utilized to improve access to such deep-seated lesions. A 62-year-old female presented with a heterogeneously enhancing lesion in the pineal region with associated hydrocephalus. On exam, the patient exhibited Parinaud’s syndrome. The patient initially underwent a single burr hole endoscopic third ventriculostomy and biopsy of the lesion. Initial pathology was consistent with a grade III astrocytoma. Following a period of recuperation, she returned for definitive surgical resection. A suboccipital craniectomy was performed in the sitting position. Prior to dural opening, an endoscope was inserted into the right lateral ventricle through the prior burr hole.The endoscope was passed through the foramen of Monro and the tumor could be visualized along the posterior third ventricle. The patient underwent a standard supracerebellar infratentorial approach aided by the microscope. After initial debulking of the pineal lesion, an endoscope was utilized to guide the depth of resection and assist in dissection with transventricular manipulation of the tumor. During the final stages of resection from the craniotomy, the endoscope was used to help visualize the posterior supracerebellar corridor. This assisted in the assessment of the extent of resection. The endoscope was also utilized for the removal of intraventricular blood products following tumor resection. The patient was extubated and transferred to the intensive care unit. A postoperative contrast-enhanced magnetic resonance imaging (MRI) revealed greater than 95% resection, with expected residual within the midbrain. The combined supracerebellar infratentorial and transventricular endoscope-assisted approach provided maximum visualization and aided in optimal resection of a traditionally difficult pineal region tumor. Further experience with this combined technique may allow for improved surgical outcomes for these complex lesions.